Answer:
B. 2.2π m² : 3.2π m²
Step-by-step explanation:
Given:
Slant height (l) = 2.2 m
Diameter (d) = 2 m
Radius (r) = ½(2) = 1 m
Required:
Lateral area and surface area
Solution:
✔️Formula for lateral area of a cone = πrl
Plug in the values
Lateral area of the cone = π*1*2.2
Lateral area = 2.2π m²
✔️ Formula for surface area of a cone = πr(l + r)
Plug in the values
Surface area of the cone = π*1(2.2 + 1)
Surface area = π(3.2)
Surface area = 3.2π m²
The answer would therefore be:
2.2π m² : 3.2π m²
Because α varies directley to β
![\alpha = k \beta](https://tex.z-dn.net/?f=%20%5Calpha%20%3D%20k%20%5Cbeta%20)
(k = constant)
α=7 when β=2
7= 2k
k=
so when α=21
21=
![\frac{7}{2}](https://tex.z-dn.net/?f=%20%5Cfrac%7B7%7D%7B2%7D%20)
b
b= 6
Answer:
Step-by-step explanation:
( 2 , 26 )
( 0 , 4 )
m = (26 - 4 ) / ( 2 - 0 ) = 11
Cost of each game is $11
Answer:
option B
Step-by-step explanation:
9/10 + 6/5 + 3/2...........
We find the difference between the terms
![\frac{6}{5} - \frac{9}{10}](https://tex.z-dn.net/?f=%5Cfrac%7B6%7D%7B5%7D%20-%20%5Cfrac%7B9%7D%7B10%7D)
![\frac{12}{10} - \frac{9}{10} = \frac{3}{10}](https://tex.z-dn.net/?f=%5Cfrac%7B12%7D%7B10%7D%20-%20%5Cfrac%7B9%7D%7B10%7D%20%3D%20%5Cfrac%7B3%7D%7B10%7D)
We will get the same difference when we subtract consecutive terms.
so , d= 3/10, a= 9/10
we find the formula for nth term
a_n = a+(n-1) d
![a_n = \frac{9}{10} + (n-1)\frac{3}{10}](https://tex.z-dn.net/?f=a_n%20%3D%20%5Cfrac%7B9%7D%7B10%7D%20%2B%20%28n-1%29%5Cfrac%7B3%7D%7B10%7D)
![a_n = \frac{9}{10} +\frac{3}{10}n-\frac{3}{10}](https://tex.z-dn.net/?f=a_n%20%3D%20%5Cfrac%7B9%7D%7B10%7D%20%2B%5Cfrac%7B3%7D%7B10%7Dn-%5Cfrac%7B3%7D%7B10%7D)
![a_n = \frac{6}{10} +\frac{3}{10}n](https://tex.z-dn.net/?f=a_n%20%3D%20%5Cfrac%7B6%7D%7B10%7D%20%2B%5Cfrac%7B3%7D%7B10%7Dn)
![a_n = \frac{3}{5} +\frac{3}{10}n](https://tex.z-dn.net/?f=a_n%20%3D%20%5Cfrac%7B3%7D%7B5%7D%20%2B%5Cfrac%7B3%7D%7B10%7Dn)
we need to find eighth partial sum so we take n=1 to 8
sum of 8 terms (
)
So option B is correct
F(0)= 5 because 3(0) is the same as 0 and you add 5 so f(0)= 5